Parámetros constitucionales en la determinación de los arbitrios en el distrito de trujillo - Rodríguez Angeles, Lenin Ernesto (2009)
The municipal taxes, isn’t voluntary, that is, the taxpayer’s will isn’t necessary to birth of this tax. On the contrary the municipal taxes are obligatory, because of the fact that, are figment of tax power to confer the municipality on behalf of Constitution. But this power isn’t unlimited but la same Constitution to establish limits of action to municipalities in tax matter; limits constitute for the tax constitucional principles. The present Thesis to opt Lawyer's Title is guided to make a study of the municipal taxes, and most specifically those to charge in our Trujillo’s locality. Study to carry through of minimum parameters establish to our supreme interpreter of Constitution. This parameters isn’t the unique, too exist others which can will use to municipalities, whenever those to guarantee a better tax justice at that moment of theirs distribution among the obliged to do pay. The central nucleus of our investigation, is precisely to study the constitutional or unconstitutional of municipal tax charge to Trujillo’s Provincial Municipality in accordance with the tax principle mentioned; principles which isn’t always applied correctly to the municipalities and caused which the Constitutional Court, in particular cases, to establish general rules to the distribution of municipal tax, this rules are obligatory to all the municipalities of country